Staying local in the global village : Bali in the twentieth century - Rubinstein, Raechelle, 1954-; Connor, Linda, 1950- (University of Hawai'i Press, 1999)
Staying Local in the Global Village is part of a continuing tradition in which Balinese and foreign scholars reflect on the processes of transformation that link Bali to Indonesia and the world beyond.